ARAKTER TOKOH KARNA DALAM CERITA PEWAYANGAN VERSI JAWA DAN SUNDA - Timbul Subagya (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2015)
The community of wayang (puppet) lovers often idolizes the characters of Mahabharata andRamayana stories. One of the idolized characters is Karna. The idolizing of Karna focuses on hiscourage in defending Korawa in the War of Bharatayuda. In Indonesia, wayang grows in severalareas with their own characteristics that create their own tradition or version of wayang. Thereare similarities as well as disparities among the traditions including the character of Karna inJavanese and Sundanese wayang as well.Keywords: puppet, Karna, Javanese, Sundanese.